2006
DOI: 10.1002/jcp.20860
|View full text |Cite|
|
Sign up to set email alerts
|

The role of MAPK in Kupffer cell toll‐like receptor (TLR) 2‐, TLR4‐, and TLR9‐mediated signaling following trauma‐hemorrhage

Abstract: Severe injury deranges immune function and increases the risk of sepsis and multiple organ failure. Kupffer cells play a major role in mediating posttraumatic immune responses, in part via different Toll-like receptors (TLR). Although mitogen-activated protein kinases (MAPK) are key elements in the TLR signaling pathway, it remains unclear whether the activation of different MAPK are TLR specific. Male C3H/HeN mice underwent midline laparotomy (i.e., soft tissue injury), hemorrhagic shock (MAP approximately 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 52 publications
(51 reference statements)
4
59
0
1
Order By: Relevance
“…p38 MAPK and JNK are two important family members that regulate the release of inflammatory mediators (Silvers et al 2003). Lipopolysaccharide promotes the production and release of a large number of inflammatory mediators through the activation of MAPK, and this has been shown to be important in the onset and progression of ALI (Thobe et al 2007;Asaduzzaman et al 2008). In our studies, NF-κB, JNK, and p38 MAPK were all elevated in ALI, and GA inhibited their expressions, offering a protective effect against sepsis.…”
Section: Discussionsupporting
confidence: 52%
“…p38 MAPK and JNK are two important family members that regulate the release of inflammatory mediators (Silvers et al 2003). Lipopolysaccharide promotes the production and release of a large number of inflammatory mediators through the activation of MAPK, and this has been shown to be important in the onset and progression of ALI (Thobe et al 2007;Asaduzzaman et al 2008). In our studies, NF-κB, JNK, and p38 MAPK were all elevated in ALI, and GA inhibited their expressions, offering a protective effect against sepsis.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have illustrated that monocytes treated with C5a produce IL-6 (37). Other studies have shown that hemorrhage increases KC, MCP-1, IL-6 and IL-10 serum concentrations in a TLR4-dependent manner (22,38,39). In addition, Meng et.al.…”
Section: Discussionmentioning
confidence: 91%
“…Many animal models of hemorrhage involve rats and include traumatic injury (19)(20)(21)(22)(23)(24) and the use of heparin (3,16) which complicates determination of the complement activation factors. In addition, rat models of hemorrhagic shock preclude the use of genetically modified animals.…”
Section: Introductionmentioning
confidence: 99%
“…PGN elevates phosphorylation of MAPKs, and MAPKs mediate chemokine production in TLR2, 4, and 9 signaling, which indicates the involvement of the kinases in CCL3 expression (Thobe et al, 2007;Lee et al, 2011). Appropriately, we investigated if MAPKs played roles in the expression of the chemokine.…”
Section: Discussionmentioning
confidence: 99%